Contextualising adolescent development: Adams, GR, Montemayor, R, & Gullotta, T P (eds) (1996) Psychosocial development during adolescence: Progress in developmental contextualism. Thousand Oaks: Sage Publications. ISBN 0-7619-0533-2 pbk. 346 pages. - Bhana, Arvin (PINS-Psychology in Society, 2026)
Psychosocial development during adolescence is part of the annual book series published by Sage and deals exclusively with advances in adolescent development. The authors have diverse academic backgrounds and research experience, and includes developmental psychologists, sociologists, psychiatrists, and graduate students. The multidisciplinary focus of this book is a singularly positive feature as many of the authors attempt to provide multiple conceptual outlooks.